Liquefaction potential assessment using SPT data - Dungca, Jonathan R. (Animo Repository, 2008)
The geotectonic setting of the Philippines makes it prone to various types of seismic related hazards. The devastating Luzon earthquake of 1990 is one of the most recent manifestations of this phenomenon and it has also opened opportunities to better understand the liquefaction phenomenon. Dagupan City suffered tremendous losses in terms of lives and properties not only because of the violent shaking of the structures but mainly because of the liquefaction of the foundation soils. Thick liquefiable sand layer predominantly underlies Dagupan City. Many areas in the Philippine archipelago including parts of Manila is believed to have similar geologic setting as in Dagupan City where deposits of potentially liquefiable sand exist and are presently used for residential, commercial or industrial purposes. It is in this premise that this study was initiated to be able to make effective liquefaction potential assessments for selected areas vulnerable to liquefaction. Detailed assessment of liquefaction potential using the semi-empirical method of Idriss and Boulanger (2004) will be presented in this paper. The method is based on the empirical relationship of standard penetration resistance and the cyclic stress ratio causing liquefaction. The borehole data such as, depth of water table, soil type, SPT N-value and unit weight of soil and earthquake data such as, magnitude and maximum ground acceleration are the input parameters in this method. The output will be a factor of safety. The factor of safety is the most important criterion in determining whether an area will liquefy or not. An actual liquefaction potential assessment will also be presented using some borehole data collected in Manila. This method will guide engineers and government planners in identifying liquefaction areas. Public and private property owners will also be guided in the development and planning infrastructures.